DEVELOPMENT OF COGNITIVE ACTIVITY OF PRIMARY SCHOOL STUDENTS BY PROJECT METHOD - Kovshar, O.V. (Pedagogy of Higher and Secondary Education, 2022)
In the article an author examines possibilities of method of projects for development of educational activity of students, forming of cognitive activity and selects the value of project activity in becoming of personality of junior schoolboy.